An empirical basis for the use of design patterns by architects in parametric design. (September 2016) - Yu, Rongrong; Gero, John S
This article presents the results from exploring the impact of using a parametric design tool on designers' behavior in terms of using design patterns in the early conceptual development stage of designing. It is based on an empirical cognitive study in which eight architectural designers were asked to complete two architectural design tasks with similar complexity, respectively, in a parametric design environment and a geometric modeling environment. The protocol analysis method was employed to study the designers' behavior. In order to explore the development of design patterns in the empirical data, Markov model analysis is utilized. Through Markov models analysis of the parametric design environment and geometric modeling environment results, it was found that there are some significantly different design patterns being used when designing in a parametric design environment compared to designing in a geometric modeling environment. The article articulates these differences and draws conclusions from these results.